ANALISIS KRITIS KEWENANGAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DALAM PENYELESAIAN SENGKETA PERUNDANG-UNDANGAN MELALUI MEDIASI - Ade Kosasih; A Majid Ali (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: The many regulations in Indonesia make it difficult to realize harmonization of law, even what happens is the opposite, namely the emergence of conflicting legal norms between laws and regulations. Conflict of norms results in legal uncertainty. Therefore, the Ministry of Law and Human Rights as the leading sector in the development of national law initiates the settlement of conflict of norms / disharmony in legislation through mediation. However, the resolution of norm conflicts through mediation is an anomaly from resolving norm conflicts that are generally known. In addition, the authority of the Ministry of Law and Human Rights as a mediator in resolving conflicting norms is also a polemic. Analysis through a conceptual approach and legislation in this paper shows that although the function of fostering national law lies with the Ministry of Law and Human Rights, the Ministry of Law and Human Rights is not authorized to resolve conflicts of laws and norms, even through mediation. The function of developing national law is only limited to evaluating the draft laws and regulations. Based on Law Number 12 of 2011 concerning Formation of Regulations and Regulations, the resolution of conflicting norms of laws and regulations under the law can only be done through judicial review to the Supreme Court. Keywords: Dispute; Regulation; Mediation